Detection of Β-Lactamase OXA Genes and Biofilm Production in Carbapenem Resistant Gram-Negative Bacilli - Amna Sarwar, Syeda Zahra Gillani, Rana Muhammad Shahbakht, Fiza Shafqat, Ajmal Nisar Mengal, Sidra Mengal, Abeera Ashraf, Zian Asif, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The emergence of carbapenem resistance in biofilm producer Gram-negative bacteria poses a substantial challenge to manage infections. This study aimed to evaluate biofilm production and molecular characterization of carbapenem resistance Gram-negative rods. Methods: Total of 46 bacteria were isolated from various clinical samples, including blood, CSF, urine, sputum, saliva, tracheal secretion, and pus. Following the standard guidelines for bacterial identification (CLSI), bacterial pathogens are isolated and identified. The antibiotic susceptibility profile was obtained against commercially available antibiotics including Amoxicillin, Amikacin, Ceftazidime, Cefepime, Imipenem, Meropenem, Gentamycin, Tobramycin, Doxycycline, Minocycline, Tazobactam, Ciprofloxacin, and Levofloxacin following CLSI guidelines. Biofilm production potential was quantified by using 96-well flat bottom microtiter plates. Phenotypic and molecular characterization of carbapenem-resistant bacteria was performed. The genotypic resistance to carbapenem was determined using OXA-23, OXA-24, OXA-51 and OXA-58 gene primers. Results: The Gram-negative bacterial strains were found as Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae, and Serratia marcescens. The phenotypic resistance against carbapenem drugs was 95%. DNA of carbapenem-resistant bacteria isolated by commercially available kit and polymerase chain reaction assay was performed and optimized to identify OXA-23 (84%), OXA-24(90%), OXA-51(83%) and OXA-58(80%) gene in bacterial strains. Practical Implication: For better and prompt management of antimicrobial resistance further work on genetics is required and warranted to produce gene effective drugs to enhance antimicrobial effect of carbapenems. Conclusion: The prevalence of carbapenem resistance among Gram-negative bacilli was high. OXA genes have raised clinical concern and further study is required to detect carbapenemase-producing bacteria. Keywords: Antibiotic Resistance, Biofilm, Carbapenem-resistance, Escherichia coli, Acinetobacter baumannii, Klebsiella pneumoniae, Serratia marcescens, β-lactamases, OXA-23, OXA-24, OXA-51 and OXA-58.